Death Penalty in The Jakarta Post and The Jakarta Globe Editorials: Neutral or Loaded? Assertive or Timid? - Siegfrieda A.S. Mursita Putri (Journal of Language and Literature, 2018)
Coming under the spotlight of the world news due to the death penalty verdict against eight drug traffickers announced early 2015, Indonesia made the world pleaded to not proceed the execution. It is interesting to see how the press media viewed this controversial issue and manifested them into linguistic features in their opinion. This paper reported views about the issue from the perspective of English newspapers. Aiming to identify the level of neutrality, certainty and assertiveness in presenting perspective, this study employed mainly qualitative method focusing on the discourse. The analysis was focused on (1) how the participants of the event were referred to, (2) lexical choices used to portray events, players and policies, and (3) modality values, orientation, manifestation and value of modality. Editorials on the issue published in selected English newspapers were collected. By applying van Dijks method, the level of neutrality was analyzed. The basis of the modality analysis was Hallidays. Both newspaper editorials showed different level of neutrality, certainty and assertiveness. There were formal and neutral choices in naming the participants of the event. The Jakarta Globe delivered their attitude using loaded words, while The Jakarta Post used more neutral and formal words in addition to using less modal forms. The study also showed the dominant use of low modality and implicitly subjective modality in presenting perspectives. This implied that the newspapers were not assertive and not strictly speaking metaphorical in delivering their perspectives to the readers.Keywords: editorial, lexical choice, modality, discourse analysis, death penalty